Model-Free Position Control for Cardiac Ablation Catheter Steering Using Electromagnetic Position Tracking and Tension Feedback - Back, Junghwan; Lindenroth, Lukas; Rhode, Kawal; Liu, Hongbin (Frontiers in Robotics and AI, 2017)
Cardiac ablation therapy is an effective minimally invasive treatment for cardiac arrhythmia. Catheter steering in the constrained environment during the procedure is considered difficult, particularly in providing accurate catheter tip positioning for ablating or for diagnosing the cardiac tissue. These difficulties and inaccuracies in the catheter tip positioning are a common reason for severe complications and a prolonged duration of the procedure. To improve the maneuverability and hence the accuracy of the catheter tip navigation, a model-free catheter tip position control with a new robotic catheter system is proposed in this article. A model-free tension control algorithm for steering the catheter has been developed and implemented in the robot. As seen in the experimental validation of the system, the model-free control is able to minimize position error up to 0.5 ± 0.2 mm from 80 mm position error within 7 ± 2 s. Furthermore, it shows the capability to react efficiently to external disturbances, such as external contacts or unwanted catheter shaft movement.